2019
DOI: 10.1016/j.athoracsur.2019.03.058
|View full text |Cite
|
Sign up to set email alerts
|

Open Descending and Thoracoabdominal Aortic Repairs in Patients Younger Than 50 Years Old

Abstract: Background. The purpose of this study was to redefine indications of open descending and thoracoabdominal aortic aneurysm repair in the younger population.Methods. Between 1991 and 2017, 2012 patients undergoing descending and thoracoabdominal aortic aneurysm repair at our institution were divided into 2 groups for comparison: younger (<50 years; 276 [14%]) and older ( ‡50 years; 1736 [86%]). Patient demographics and perioperative outcomes were retrospectively reviewed.Results. Younger patients had significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 18 publications
(19 reference statements)
0
12
0
1
Order By: Relevance
“…Open repair for any segment of the thoracic aorta has proven to be durable in extended follow-up. 10,11,13,14,19 Treatment failure after open repair of either the proximal or distal thoracic aorta requiring reintervention ranges from 1% to 7% in long-term (10-year) follow-up. 10-12 In patients without a genetic syndrome or residual aortopathy shown on a postoperative imaging, surveillance can be done at longer intervals.…”
Section: Aneurysmsmentioning
confidence: 99%
“…Open repair for any segment of the thoracic aorta has proven to be durable in extended follow-up. 10,11,13,14,19 Treatment failure after open repair of either the proximal or distal thoracic aorta requiring reintervention ranges from 1% to 7% in long-term (10-year) follow-up. 10-12 In patients without a genetic syndrome or residual aortopathy shown on a postoperative imaging, surveillance can be done at longer intervals.…”
Section: Aneurysmsmentioning
confidence: 99%
“…7 Another singlecenter retrospective observational study in the United States reported that paraplegia/paraparesis occurred in 8.3% of 2,012 patients who underwent open descending and thoracoabdominal aortic aneurysm repair between 1991 and 2012. 8 In the study population, which did not include abdominal or thoracoabdominal aortic aneurysms, paraplegia occurred in less than 3% of both surgery groups. This was similar to the findings of Lou et al, which reported that postoperative paraplegia occurred in 3.4% of open surgical repair patients and 2.3% of TEVAR patients with type B aortic dissection.…”
Section: Discussionmentioning
confidence: 95%
“…Es ergeben sich daraus aber auch nach wie vor klare Indikationen, die ein offenes Vorgehen rechtfertigen bzw. klar indiziert erscheinen lassen: ▪ Junges Patientenalter: Patienten < 50(-60) Jahre verkraften nicht nur ein OR besser, sie haben auch geringere Komplikationsraten und profitieren darüber hinaus vor allem aufgrund der geringen Re-Interventionsraten und Langzeitkomplikationen von einem offenen Vorgehen[23,24]. ▪ Bindegewebserkrankungen: In dieser Patientengruppe (z. B.Marfan-, Loyes-Dietz-oder vaskuläres Ehlers-Danlos-Syndrom) stellt aufgrund der speziellen Veränderungen des aortalen Bindegewebes das OR noch immer den Goldstandard dar[25].Allenfalls im Notfall hat hier die endovaskuläre Therapie einen Stellenwert, wobei dies nur als Bridging bis zu einer definitiven Therapie betrachtet wird [26].…”
unclassified